Effect of Al2O3 on electrical properties of polymer electrolyte for electrochemical device application. (2021) - Nidhi,; Patel, Sandhya; Kumar, Ranveer
Abstract: Polyvinylideneflouride (PVDF) based nanocomposite polymer electrolyte (NCPE) thin films consist of magnesium nitrate as ionic salt and aluminium oxide nanoparticles as nano-filler has been synthesized by solution casting technique. The electrical, structural, thermal, transport and discharge properties of synthesized films were characterized by Impedance Spectroscopy, X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) Spectroscopy, Differential Scanning Calorimetry-Thermal Gravimetric Analysis (DSC-TGA) and Wagner's DC polarization technique respectively. Complexation was done in polymer electrolyte films were confirmed by XRD and FTIR studies. Composition dependant conductivity studies of films give highest conductivity value for composition: 70PVDF:30 Mg(NO3 )2 : 2Al2 O3 i.e. σ 1.01 × 10 −4 S/cm. Thermal stability of polymer electrolyte was confirmed by DSC-TGA. Transport number (tion 1) has been calculated from polarization technique. A test cell fabricated for OCC of NCPE in cell configuration Mg| NCPE| C cell and various parameters have been calculated.